2020
DOI: 10.1038/s41467-020-19191-0
|View full text |Cite
|
Sign up to set email alerts
|

Distinct CCK-positive SFO neurons are involved in persistent or transient suppression of water intake

Abstract: The control of water-intake behavior is critical for life because an excessive water intake induces pathological conditions, such as hyponatremia or water intoxication. However, the brain mechanisms controlling water intake currently remain unclear. We previously reported that thirst-driving neurons (water neurons) in the subfornical organ (SFO) are cholecystokinin (CCK)-dependently suppressed by GABAergic interneurons under Na-depleted conditions. We herein show that CCK-producing excitatory neurons in the SF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 71 publications
1
24
0
Order By: Relevance
“…When AAV-DIO-mCherry was stereotaxically injected into the SFO of CCK-Cre mice, mCherry-positive cells in the SFO (CCK-positive cells) overlapped with nNOS-immunoreactive cells, indicating that they belong to excitatory neurons in the SFO. 138 ) The findings of qPCR also revealed significantly higher CCK mRNA levels (∼2.1-fold) in the SFO in Na-depleted conditions than in control conditions, suggesting the up-regulation of CCK in CCK-positive neurons in the SFO. 138 )…”
Section: Water Intake Controlmentioning
confidence: 78%
See 2 more Smart Citations
“…When AAV-DIO-mCherry was stereotaxically injected into the SFO of CCK-Cre mice, mCherry-positive cells in the SFO (CCK-positive cells) overlapped with nNOS-immunoreactive cells, indicating that they belong to excitatory neurons in the SFO. 138 ) The findings of qPCR also revealed significantly higher CCK mRNA levels (∼2.1-fold) in the SFO in Na-depleted conditions than in control conditions, suggesting the up-regulation of CCK in CCK-positive neurons in the SFO. 138 )…”
Section: Water Intake Controlmentioning
confidence: 78%
“…To clarify the location of CCK-producing cells, we measured CCK concentration ([CCK]) in blood and SFO tissues in water- and Na-depleted conditions. 138 ) Plasma [CCK] remained unchanged between the different conditions, whereas [CCK] in the SFO was markedly higher in Na-depleted conditions than in control conditions (∼9.0-fold). When AAV-DIO-mCherry was stereotaxically injected into the SFO of CCK-Cre mice, mCherry-positive cells in the SFO (CCK-positive cells) overlapped with nNOS-immunoreactive cells, indicating that they belong to excitatory neurons in the SFO.…”
Section: Water Intake Controlmentioning
confidence: 85%
See 1 more Smart Citation
“…Water deprivation reduces the volume and increases the osmolality of an animal’s hemolymph or blood. These changes induce multiple adaptations throughout the body, such as changes in the activity of osmosensory nuclei in the brain (the LT in mammals and ISNs in Drosophila ) as well as production and release of neuropeptide or neurohormone modulators (Augustine et al, 2020; Gáliková et al, 2018; Jourjine et al, 2016; Landayan et al, 2021; Matsuda et al, 2020; Senapati et al, 2019; Zimmerman et al, 2017). These molecules modulate organs controlling water retention, excretion and blood pressure, and the activity of neuronal circuits.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified multiple molecularly-or anatomically-distinct neuronal populations in the LT that are involved in different aspects of water homeostasis (Oka et al, 2015b;Abbott et al, 2016;Allen et al, 2017;Matsuda et al, 2017;Augustine et al, 2018;Matsuda et al, 2020;Pool et al, 2020). In this study, we investigated the role of the LT neurons in mediating presystemic regulation of AVP neurons.…”
Section: Discussionmentioning
confidence: 99%